Neoadjuvant chemotherapy of patients with early breast cancer is associated with increased detection of disseminated tumor cells in the bone marrow - Volmer, Léa; Koch, André; Matovina, Sabine; Dannehl, Dominik; Weiss, Martin; Welker, Ganna; Hahn, Markus; Engler, Tobias; Wallwiener, Markus; Walter, Christina; Oberlechner, Ernst; Brucker, Sara; et al. (Cancers, 2022)
Preclinical data suggest that neoadjuvant chemotherapy (NAT) may promote micrometastatic spread. We aimed to compare the detection rate and prognostic relevance of disseminated tumor cells (DTCs) from the bone marrow (BM) of patients with early-stage breast cancer (EBC) after NAT with that of therapy-naive EBC patients. DTCs were identified from BM samples, collected during primary surgery. Patients who received NAT were compared to patients who received chemotherapy after surgery. In total, 809 patients were analyzed. After NAT, 45.4% of patients were DTC-positive as compared to 19.9% of patients in the adjuvant chemotherapy group (p < 0.001). When sampled in patients who had undergone NAT, the detection of DTCs in the BM was significantly increased (OR: 3.1; 95% confidence interval (CI): 2.1-4.4; p < 0.001). After NAT, DTC-positive patients with ≥2 DTCs per 1.5 × 106 mononuclear cells in their BM had an impaired disease-free survival (HR: 4.8, 95% CI: 0.9-26.6; p = 0.050) and overall survival (HR: 4.2; 95% CI: 1.4-12.7; p = 0.005). The higher rate of DTC-positive patients after NAT as compared to a treatment-naive comparable control cohort suggests that NAT supports tumor cell dissemination into the bone marrow. DTC positivity in BM predicted relapse in various distant organs, implying that tumor cell dissemination was not restricted to the bone marrow.